AB1030 IgG4-RELATED DISEASE: A RETROSPECTIVE CLINICAL CASE SERIES FROM A TERTIARY CARE CENTRE IN INDIA. (2nd June 2020) - Gupta, M.; Duggal, L.; Gurbir Singh, B.; Patel, J.; Jain, N.; Grover, A. K.
Abstract : Background: IgG4-related disease (IgG4-RD) is an often unrecognized, rare fibro-inflammatory condition that can involve various organ systems. Objectives: The aim of this study was to identify the different clinical patterns of this disease in a single centre in North India. Methods: 70 patients were diagnosed on the basis of published diagnostic criteria for IgG4-RD. Patients' presenting complaints, epidemiological profiles, laboratory, radiological and histological findings along with the treatment and outcomes were collated and analyzed from 2011 – 2019. Results: In a total of 70 patients who were diagnosed with the disease, the ratio of female to male ratio was 1:1. The mean age of patients was 41.4 years. Involvement of orbits and peri-orbital tissues was highest (52.9%) due to large number of referrals from ophthalmology services. 13% of patients had multiple organ involvement. Patients with involvement of retroperitoneal tissues and lymph nodes were 8.5% and 5.7%, respectively. Increased serum IgG4 levels were found in 74.3% of the patients. Histopathological examinations of the affected organs were performed in 44 (62.85%) patients and a diagnosis of possible (38.57), probable (32.85%) and definite (28.57%) IgG4-RD was made. Majority of the patients (94.3%) required immunosuppressive medications along with corticosteroids. Azathioprine was the most commonly used (72.8%) immunosuppressive medication. Rituximab was used in17.1% of the patients, of whom one had multisystem involvement. Conclusion: This study depicts the most common patterns of organ involvement along with the epidemiological, laboratory, histological, radiological data and response to treatment, in IgG4-RD, with a definite ophthalmology referral bias, in a tertiary care centre in North India. References: [1]Stone JH, Zen Y, Deshpande V. IgG4-related disease. N Engl J Med 2012; 366(6):539-51. [2]Khosroshahi A, CarruthersMN, Deshpande V, Unizony S, Bloch DB, Stone JH. Rituximab for the treatment of IgG4-related disease: lessons from 10 consecutive patients. Medicine 2012; 91(1):57-66. Disclosure of Interests: None declared